Expression patterns of hair-related keratins and epithelial keratins in onychopapilloma: The significance of clarifying the origin of onychopapilloma - Liu, Mengxi; Li, Fang; Wang, Xiaoqing; Liu, Zhenru; Wong, Hoi Shiwn; Zhou, Yuan; Wang, Daguang (Frontiers in Medicine, 2022)
Background: Onychopapilloma is generally recognized as a benign tumor of the nail bed and distal matrix. However, the origin of onychopapilloma has not been explained yet. Objective: To clarify the origin of onychopapilloma, we detected the expression patterns of hair-related keratins and epithelial keratins, which are expressed specifically in the nail unit. Materials and methods: The clinical and histopathologic features of 11 patients with onychopapilloma were analyzed, and the expression patterns of hair-related and epithelial keratins were detected. Results: Histologically, all subjects showed acanthosis, papillomatosis and matrix metaplasia within the nail bed. Immunohistochemically, the expression pattern of keratins in our standard nail unit was consistent with previous reports. "Nail matrix-related keratins" HK31, HK34, HK85 and HK86 were only expressed in the nail matrix, and "Nail bed-related keratins" HK75 and K6/K16 were only expressed in the nail bed. However, in onychopapilloma, whether adjacent to the matrix or in the distal nail bed, all cases were positive for nail bed-related keratins and HK31 but negative for other nail matrix-related keratins. Conclusion: Our study suggests that onychopapilloma may originate from the nail bed rather than the nail matrix. Furthermore, the expression of nail bed-related keratins and HK31 could be used as diagnostic markers of onychopapilloma.